PENGARUH TEMPAT TUMBUH, JENIS DAN DIAMETER BATANG TERHADAP PRODUKTIVITAS POHON PENGHASIL BIJI TENGKAWANG - Ina Winarni; E S Sumadiwangsa; Dendy Setyawan (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Tengkawang is one of the leading commodity of non timber forest products in West Kalimantan. Tengkawang commodity ls sold in the form of dry seed mainly for export. Meanwhile, the processed products derived from tengkawang such as tengkawang oil are sent back to Indonesia as imported finished and half-finished items. This investigation was mainly aimed at assessing the effect of growth site, species, and diameter of tengkawang producing trees on the seed productivity. The target was to procure reliable data/information on productivity and technical growth increment which can befurther useful as a guidance in developing tengkawang-seed busines. The result revealed that the highest productivity of tengkawang seeds indicated by the trees with a diameter in the range of 60 -90 cm. The results revealed that, the seed production was 555,7 kg per tree per harvest. The highest seed productivity was indicated by Shorea stenoptera Burk trees growing in Sanggau, i.e. 620,9 kg per trees per harvest. It is suggested that based on the honestly significant difference's range test, the promising development of tengkawang cultivation in rank by species from the most until the least was consecutively Shorea stenoptera Burk, Shorea stenoptera Burk Forma Ardikusuma, and Shorea palembanica Miq. respectively, All species grow in Sintang and Sanggau.